Presupposition Analysis in David Cameron’ Speech for Conservative Party Conference - Widyashanti Kunthara Anindita (Musamus Journal of Language and Literature, 2021)
This research explains about presuppositions in a speech. The purposes are to find out types of presuppositions, to analyze meanings of each presupposition in, and to find out situation used by the speaker to apply presupposition. The writer used the theory of George Yule (1996). For data, the writer used two scripts of David Cameron speech in October 2014 and 2015. The writer used the approach of descriptive qualitative research method. As population, the writer took the utterances containing presupposition in the form of phrases and sentences. As sample, the writer took Purposive Sampling Technique. To collect the data, the writer used observation and taking note method. To analyze the data, the writer use basic distributional method. To prove the valid data, the writer used source triangulation method. The writer found 164 presuppositions. There are 50 for existential presupposition situated in noun phrase, 33 for factive presupposition situated in fact information, 10 for non-factive presupposition situated in falsity information, 10 for lexical presupposition situated in asserted meaning understood, 13 for structural presupposition situated on wh-question, and 46 for counterfactual presupposition situated in ‘if’. The writer concluded that the most presuppositions found in this research is existential presupposition and the least ones are non-factive and lexical presupposition.